Screening of Superior Lactic Acid Bacteria in Persimmon Vinegar Broth and Analysis of Its Tolerance and Function - Shiyang JIAO; Xiaotong WANG; Yuxin HOU; Mengyang WANG; Mingqiang CHEN; Yanhui YANG; Dahong WANG (Shipin gongye ke-ji, 2023)
In order to obtain lactic acid bacteria (LAB) with a strong acid production capacity, good tolerance, and high function from persimmon vinegar broth, which is suitable for plant substrate fermentation. Using the persimmon vinegar broth naturally fermented as a source of lactic acid bacteria, five strains were isolated using MRS liquid culture medium and calcium-dissolving circle methods. The abilities of producing acid, tolerance, antioxidant and β-glucosidase production of the 5 LABs were measured, the morphology and 16S rDNA identification of the screened two LABs with stronger comprehensive performance were analyzed. Based on the results of the screening, Lactobacillus acidophilus and Lactobacillus plantarum were identified as two excellent strains of lactic acid bacteria. Both lactic acid bacteria produced acid at a rate of 2.00 and 2.24 g/100 mL, respectively. Among the pH tolerances, the lowest was 1.5, the highest was 10% for ethanol, 1% for bile salts, and 7% for NaCl. The scavenging abilities of screened two LABs on ABTS+, DPPH, O2- free radicals were 65.12% and 62.26%, 77.42% and 68.89%, 93.76% and 87.89%, respectively. The production of β-glucosidase were 26.37 and 30.27 IU/L. In this paper, the two LABs strains with strong biological properties were obtained from persimmon vinegar broth for plant substrate fermentation, which could provide strain resources for the development of probiotics.